Development and Acceptability of Tuyong Tawilis (Sardinella tawilis) Flavored Noodle - Lazaro, John Marco A.; Maroma, Dolly P.; Maroma, Allen N. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
This study examines the role of food innovation in the global noodle market, particularly addressing the nutritional limitations of many instant noodle products. It emphasizes the need for healthier alternatives to meet the growing demand from health-conscious consumers. Specifically, the study advocates for the development of high-protein noodle variants enriched with local flavors, such as "Tuyong Tawilis" (dried Sardinella tawilis), to enhance both nutritional value and market appeal. The innovative noodle variant's quality and safety are ensured by thorough evaluations that involve sensory analysis, physico-chemical, and microbiological investigation. This highlights the importance of flavor theory and new product development in meeting consumer preferences and promoting innovation. The study uses a quantitative approach with 220 respondents—experts and students—selected by convenience sampling to create, execute, and assess the "tuyong tawilis" flavored noodles. The research methodically applies the Input-Process-Output (IPO) Model. The results indicate "tuyong tawilis"'s potential as a major flavoring component and physicochemical as well as microbiological analysis verify its safety and adherence to consumption guidelines. Sensory assessments support the created product's acceptance by showing a moderate like for a variety of features. In summary, the study presents a novel and well-received flavored noodle product that satisfies changing customer preferences without sacrificing quality or safety. It helps the dynamic food business by combining traditional local flavors with contemporary tastes. It also offers potential pathways for healthier and more pleasant noodle alternatives, helping to shape the continuous evolution of culinary goods in the market.